Review of Sherlock Holmes The Complete Novels and Stories - Ambarrini, Benedicta Keisya (Faculty of Law Universitas Negeri Semarang, 2021)
The Sherlock Holmes stories were the source of modern crime-solving adaptations that we now experience in television, and Doyle's tales of mystery and adventure were often audacious, insightful and clever. The real draw of his stories is the process of crime detection, that Doyle allows the readers to understand, experience and apply themselves alongside Watson as Holmes investigates the cases.